Academic freedom, private-sector focus, and the process of innovation - Aghion, Philippe 1956-; Dewatripont, Mathias; Stein, Jeremy C. 1960- (Working paper series / National Bureau of Economic Research, 2005)
We develop a model that clarifies the respective advantages and disadvantages of academic and private-sector research. Our model assumes full protection of intellectual property rights at all stages of the development process, and hence does not rely on lack of appropriability or spillovers to generate a rationale for academic research. Instead, we focus on control-rights considerations, and argue that the fundamental tradeoff between academia and the private sector is one of creative control versus focus. By serving as a precommitment mechanism that allows scientists to freely pursue their own interests, academia can be indispensable for early-stage research. At the same time, the private sectorﾒs ability to direct scientists towards higher-payoff activities makes it more attractive for later-stage research.